The Effectiveness of Quizlet in Improving Vocabulary Mastery of Junior High School Students - Rozita Nur Saharani; Rahayu Kuswardani (SEAMEO QITEP in Language, 2025)
This study investigates the effectiveness of Quizlet, a digital flashcard-based learning platform, in improving the vocabulary mastery of junior high school students, particularly in learning collocations within descriptive texts. Using a quantitative quasi-experimental design, two seventh-grade classes from a public junior high school were selected as the control and experimental groups. The experimental group received vocabulary instruction through Quizlet, while the control group used conventional methods. Data were collected using Pre-Test and Post-Test instruments that included multiple-choice and matching questions designed to assess students’ understanding of collocations. Although the independent samples t-test result showed no statistically significant difference between the two groups (p > 0.05), gain score analysis revealed a higher mean improvement in the experimental group. The findings suggest that Quizlet positively influenced vocabulary acquisition, particularly in enhancing engagement and retention through its interactive features. The study contributes to the integration of technology in English language teaching, offering insights into how digital tools like Quizlet can enrich vocabulary instruction, support the Merdeka Curriculum, and address learners' digital tendencies in today’s classrooms.